2018
DOI: 10.1111/idh.12376
|View full text |Cite
|
Sign up to set email alerts
|

A culture shock in dental hygiene: Exploring the management of oral health after head and neck cancer

Abstract: Objectives Managing oral health after the treatment for head and neck cancer requires meticulous daily oral hygiene practices and regular professional dental care; however, the individual factors and health system structures required to achieve oral health are often not well considered. This study aimed to explore how oral health was understood and managed after head and neck cancer treatment and identify factors that influenced oral health behaviours and dental service utilization. Methods A qualitative, indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 32 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…The participants presented various medical conditions and disabilities. Ten qualitative studies were found for individuals with cognitive or physical impairment, [34][35][36][37][38][39][40][41][42][43] six for people with mental illness, [46][47][48][49][50][51] five for elderly persons with comorbidities, [24][25][26][27][28] three for adults with dementia, [31][32][33] two for persons who had received head and neck cancer treatment, 44,45 two for individuals in palliative care, 52,53 one for adults with cardiovascular disease, 30 , one for stroke survivors. 29 The data extracted did not bring to light similarities or differences between the population subgroups.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The participants presented various medical conditions and disabilities. Ten qualitative studies were found for individuals with cognitive or physical impairment, [34][35][36][37][38][39][40][41][42][43] six for people with mental illness, [46][47][48][49][50][51] five for elderly persons with comorbidities, [24][25][26][27][28] three for adults with dementia, [31][32][33] two for persons who had received head and neck cancer treatment, 44,45 two for individuals in palliative care, 52,53 one for adults with cardiovascular disease, 30 , one for stroke survivors. 29 The data extracted did not bring to light similarities or differences between the population subgroups.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Eleven studies reported the perspective of the participant's family members and carers. 29,30,33,37,38,[40][41][42][43]45,53 Four studies did not involve the subjects in the interviews. 32,[34][35][36] The characteristics of the populations and the study designs are detailed and presented in Table 2.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations